2015
DOI: 10.1016/j.ophtha.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Diplopia and Ptosis from Removal of the Orbital Roof in Pterional Craniotomy

Abstract: Purpose To describe a newly recognized clinical syndrome consisting of ptosis, diplopia, vertical gaze limitation, and abduction weakness that can occur following orbital roof removal during orbito-zygomatic-pterional craniotomy. Design Case series. Participants Eight study patients, ages 44 – 80 years, 7 female, with neuro-ophthalmic symptoms after pterional craniotomy. Methods Case description of eight study patients. Main Outcome Measures Presence of ptosis, diplopia, and gaze limitation. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 43 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Moreover, the muscle can be prone to mechanical restriction from alterations in the bony anatomy and/or implant placed for reconstruction that result in a step-off or ridge as demonstrated in this series. Desai, et al also did report adhesion of the lateral rectus muscle to the osteotomy following lateral wall removal, further supporting the significance of the surgical anatomy in this complication [ 5 ].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Moreover, the muscle can be prone to mechanical restriction from alterations in the bony anatomy and/or implant placed for reconstruction that result in a step-off or ridge as demonstrated in this series. Desai, et al also did report adhesion of the lateral rectus muscle to the osteotomy following lateral wall removal, further supporting the significance of the surgical anatomy in this complication [ 5 ].…”
Section: Discussionmentioning
confidence: 90%
“…Although neurosurgical access to SWMs has improved with the FTOZ approach, ophthalmologic risks associated with resection and reconstruction of the roof and lateral wall of the orbit include enophthalmos, vision loss, ocular misalignment, and diplopia. Earlier studies attributed extraocular muscle restriction to physical injury of the muscle or respective cranial nerve during surgery, postoperative edema, and soft-tissue adhesion to the lateral wall osteotomy [ 3 - 5 ]. Liu, et al reported limitation of extraocular muscle in 40.5% (15/37) of patients after a pterional approach, which was transient in nature in 73.3% of cases and attributed to excessive traction during surgery [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reported neuro-ophthalmic complications in the setting of orbitozygomatic and fronto-temporal craniotomy include cosmetic deformity, enophthalmos, pulsatile exophthalmos, ptosis, diplopia, vertical gaze limitations and blindness (10, 11). Poor cosmetic and structural outcomes often stem from suboptimal reconstruction of a defect in the temporal region (12) and we add masticatory proptosis and oscillopsia to the list of complications.…”
Section: Discussionmentioning
confidence: 99%